A constitutional perspective on religious education in public schools in Salta, concerning the case “Castillo et al. vs. Salta” - Riccardi, María Soledad (Prudentia Iuris, 2017)
This essay reviews the unconstitutionality claim made to the laws that establish and regulate religious education in the public schools of the province of Salta, as proposed for analysis in the case “Castillo y otros v. Salta”. A group of mothers and civil associations decided to bring a protective action to prevent their children from receiving religious education; this paper and the case it quotes seek to analyze the interpretation of section 2º of the National Constitution along with other constitutional laws, to elucidate whether section 49 of the Constitution of Salta and Local Education Law 7.546 violate constitutional rights. States right to give themselves their own laws, the characteristics of federal judicial review, and class actions effects’ are also addressed